Vicarious Liability under the Indonesian Criminal Code: A Living Law Perspective from Yogyakarta: Vicarious Liability Dalam KUHP Nasional Dikaji dari Perspektif Living Law di Yogyakarta - Sahran Hadziq; Gatot Sugiharto (Universitas Islam Indonesia, 2024)
The National Criminal Code as the brand-new Indonesian criminal law’s face provides several fundamental changes, including provisions on the principle of material legality and vicarious liability. The principle of material legality provides space for living law to be the basis for the implementation of criminal law, including in determining criminal liability. Vicarious liability is a form of criminal liability that eliminates mistakes and is interpreted as substitute liability, namely that everyone can be held accountable for the actions of others. The perspective of living law is essentially very broad so each society has different characteristics and provisions. Provisions on vicarious liability based on living law can be found in the early civil law as a form of living law in Yogyakarta. This study aims to provide an understanding of the regulation of vicarious liability in Indonesian criminal law and to examine the regulation of vicarious liability based on the perspective of living law contained in early civil law. This study is an empirical legal study using a historical and philosophical approach. The data used in this study are primary and secondary data using interview methods and literature studies which are then analyzed descriptively qualitatively. The results of this study explain the differences in understanding of vicarious liability. Indonesian criminal law through the National Criminal Code understands vicarious liability only as a